PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP MINAT BELI AIR MINUM DALAM KEMASAN MEREK LE MINERALE PADA PELANGGAN ALFAMIDI GATOT SUBROTO MEDAN - Hadi Tyo Hidayat; Cahyo Pramono; M.Isa Indrawan (Ensiklopedia Education Review, 2021)
This research was conducted to determine the effect of product quality and advertisements on the interest in buying bottled drinking water with the Le Minerale brand at Alfamidi Gatot Subroto Medan. The main problem in this research was the decline in the Top Brand Index of the Le Minerale brand so that it was difficult to compete with its competitors. The population in this research amounted to 120 consumers with the number of samples determined by the Slovin formula. Samples taken were 93 respondents. This research used an associative approach with quantitative data processed with the SPSS version 24.0 application. The data source used was primary data which is taken directly from respondents through a questionnaire. The analytical model used was multiple linear regression. The research was conducted in 2022. The results showed that product quality and advertising had a positive and significant effect both partially and simultaneously on the interest in buying bottled drinking water in the Le Minerale brand at Alfamidi Gatot Subroto Medan, where the advertising variable was the most significant variable dominant influence on buying interest. Product quality and advertisements contributed 84.0% in the formation of interest in buying bottled drinking water with the Le Minerale brand at Alfamidi Gatot Subroto Medan. Product quality and advertisements also had a very strong relationship with the interest in buying bottled drinking water from the Le Minerale brand at Alfamidi Gatot Subroto Medan.Keywords: Product Quality, Advertising, and Purchase Interest.